Optimal cut-Off values of visceral fat area for predicting metabolic syndrome among type 2 diabetes patients in Ningbo, China - Yang, Xi; Lin, Yi; Xu, Guo-dong; Chen, Yan-shu; Zhou, Ye; Sun, Jing; Li, Li (Dove Medical Press Ltd, 2021)
Objective: To examine the optimal cut-off values of visceral fat area (VFA) for predicting metabolic syndrome (MetS) among type 2 diabetes (T2D) patients in Ningbo China. Methods: A total of 1017 subjects were selected from T2D patients who accepted standardized management by the National Standardized Metabolic Disease Management Center at Ningbo First Hospital from March 2018 to January 2020. Demography and medical information were collected through questionnaires. Regional adiposity was examined by a visceral fat analyzer using the dual bioelectrical impedance method. Results: Overall, 769 (75.6%) T2D patients were defined to have MetS. Patients with MetS had higher anthropometric values and biomarkers, compared to those without MetS. VFA was significantly correlated with risk factors of MetS. Further logistic regression models showed that VFA was significantly associated with MetS in men (OR=1.02) and in women (OR=1.03) (P<0.001 for both genders) after controlling for related factors. Receiver-operating characteristic curve analysis demonstrated that the optimal cut-off values of VFA were 84.7 cm2 for men and 81.1 cm2 for women to predict MetS in T2D patients. Conclusion: VFA was associated with MetS and could be an independent predictor of MetS in T2D patients. Clinical Trial Registration: Www.ClinicalTrials.gov, number: NCT03811470.